2022
DOI: 10.3390/jcm11061566
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Residual Low Back Pain after Osteoporotic Vertebral Fractures

Abstract: Although osteoporotic vertebral fractures (OVFs) are the most common type of osteoporotic fracture, few reports have investigated the factors contributing to residual low back pain in the chronic phase after OVFs by using radiographic evaluation. We examined the contribution of nonunion, vertebral deformity, and thoracolumbar alignment to the severity of residual low back pain post-OVF. This post hoc analysis of a prospective randomized study included 195 patients with a 48-week follow-up period. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A total of 86% of our patients initiated anti-osteoporosis treatment after new OVFs, and 49.3% used anabolic agents. Several previous studies on the conservative management of OVFs did not incorporate anabolic agents, leading to a presumed lower incidence of subsequent domino OVFs in the current study [ 3 , 6 , 12 , 22 , 23 ]. However, the results of this study indicate that anti-osteoporosis treatment did not prevent domino OVFs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A total of 86% of our patients initiated anti-osteoporosis treatment after new OVFs, and 49.3% used anabolic agents. Several previous studies on the conservative management of OVFs did not incorporate anabolic agents, leading to a presumed lower incidence of subsequent domino OVFs in the current study [ 3 , 6 , 12 , 22 , 23 ]. However, the results of this study indicate that anti-osteoporosis treatment did not prevent domino OVFs.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the possibility of an earlier onset of domino OVFs, assessing the clinical outcome at 1 month would be challenging as it would be difficult to discriminate between the source of pain arising from the initial OVF and that from the domino OVFs. Several recent studies have reported that pain and QOL significantly improve after 3 months of conservative treatment for OVFs [ 11 , 21 , 22 ]. Therefore, our study evaluated clinical outcomes and image assessments at the 3-month mark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis is a condition of the bones characterized by decreased bone density and compromised bone architecture, leading to a higher susceptibility to bone fractures [ 2 , 3 ]. The most prevalent form of fracture caused by osteoporosis is osteoporotic vertebral compression fracture (OVCF) [ 4 , 5 ], with ∼1.4 million new cases estimated each year globally [ 6 ]. OVCF is primarily characterized by severe low back pain, which can severely limit mobility, significantly diminish the patient’s quality of existence and even pose a risk of fatality [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite conservative treatment, residual back pain and neurological deficit are observed due to nonunion, severe deformity, and global spinal imbalance [ 13 - 15 ]. Particularly, nonunion is strongly associated with residual back pain compared to local alignment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%